Glycogen as a Putative Target for Diagnosis and Therapy in Brain Pathologies. (4th September 2011) - Cloix, Jean-François; Hévor, Tobias
Abstract : Brain glycogen, a glucose polymer, is now considered as a functional energy store to the brain. Indeed, when neurons outpace their own possibilities to provide themselves with energy, astrocytic metabolism is in charge of feeding neurons, since brain glycogen synthesis is mainly due to astrocyte. Therefore, malfunctions or perturbations of astrocytic glycogen content, synthesis, or mobilization may be involved in processes of brain pathologies. This is the case, for example, in epilepsies and gliomas, two different situations in which, brain needs high level of energy during acute or chronic conditions. The purpose of the present paper is to demonstrate how brain glycogen might be relevant in these two pathologies and to pinpoint the possibilities of considering glycogen as a tool for diagnostic and therapeutic approaches in brain pathologies.